Locating Maldivian Women's Mosques in Global Discourses - Fewkes, Jacqueline H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this ethnographic examination of women's mosques in the Maldives, anthropologist Jacqueline H. Fewkes probes how the existence of these separate buildings-where women lead prayers for other women-intersect with larger questions about gender, space, and global Muslim communities. Bringing together ethnographic insight with historical accounts, this volume develops an understanding of the particular religious and cultural trends in the Maldives that have given rise to these unique socio-religious institutions. As Fewkes considers women's spaces in the Maldives as a practice apart from contemporary global Islamic customs, she interrogates the intersections between local, national, and transnational communities in the development of Islamic spaces, linking together the role of nations in the formation of Muslim social spaces with transnational conceptualizations of Islamic gendered spaces. Using the Maldivian women's mosque as a starting point, this book addresses the roles ofboth the nation and the global Muslim ummah in locating gendered spaces within discourses about gender and Islam.
Keywords: Ethnology; Religion and sociology; Ethnology -- Asia; Culture; Islam; Sociocultural Anthropology; Ethnography; Sociology of Religion; Asian Culture; Islam